Synthesis And Characterization of Biodegradable Foam (Biofoam) From Taro Starch (Colocasia Aesculenta)-Chitosan - Azizati, Zidni; Rohmatun Nisa, Umi; Khofya Haqiqi, Arghob (Jurnal Riset Kimia, 2024)
Biodegradable foam can be used as an alternative packaging which is safe for health and environment. The raw material used to produce biofoam is starch. Taro consist of 67.42% starch. Contrarily, biofoam produced from starch has fragile mechanical properties. The addition of chitosan aims to improve the mechanical properties of biodegradable foam. Beside that, Chitosan is expected to reduce water absorption and increase tensile strength of biodegradable foam without reducing degradability. Biodegradable foam was synthesized by three steps, first step was isolation of starch from taro, second step was synthesis of biodegradable foam from taro starch-chitosan which used various concentration of chitosan to study the effect of chitosan addition for mechanical properties of biodegradable foam. Various concentration of chitosan was 0%, 1%, 2%, 3%, and 4% (w/w). Third step was characterization of biodegradable foam.  The Analysis of biodegradable foam was carried out included FTIR functional group, mechanical properties, biodegradability and water absorption. The result showed that the best tensile strength test was 1% chitosan addition with a value of 3.75 MPa; based on water absorption test, the optimum sample was 4% chitosan addition with a value of 11.66%. The results of the functional group analysis of FTIR biodegradable foam contained of C=O (amide), CN, NH and OH groups which indicated the existence of chitosan in the sample.